A DFT study on enhanced adsorption of H2 on Be-decorated porous graphene nanosheet and the effects of applied electrical fields. (27th January 2021) - Liu, Yuhang; Zhou, Yumeng; Yang, Shulin; Xu, Huoxi; Lan, Zhigao; Xiong, Juan; Wang, Zhao; Gu, Haoshuang
Abstract: The adsorption of the hydrogen molecule on the pure porous graphene nanosheet (P-G) or the one decorated with Be atom (Be-G) was investigated by the first-principle DFT calculations. The Be atom was adsorbed on the P-G with a binding energy of −1.287 eV to successfully establish the reasonable Be-G. The P-G was a poor substrate to interact weakly with the H2, whereas the Be-G showed a high affinity to the adsorbed H2 with an enhanced adsorption energy and transferred electrons of −0.741 eV and 0.11 e, respectively. A molecular dynamics simulation showed that the H2 could also be adsorbed on the Be-G at room temperature with a reasonable adsorption energy of −0.707 eV. The interaction between the adsorbed H2 and the Be-G was further enhanced with the external electrical fields. The applied electrical field of −0.4 V/Å was found to be the most effective to enhance the adsorption of H2 on the Be-G with the modified adsorption energy and the improved transferred electrons being −0.708 eV and 0.17 e, respectively. Our study shows that the Be-G is a promising substrate to interact strongly with the H2 and could be applied as a high-performance hydrogen gas sensor, especially under the external electrical field. Graphical abstract: Image 1 Highlights: Be atom can be adsorbed on porous graphene (P-G) to build the modified one (Be-G). The Be-G shows a higher affinity to the H2 compared with the P-G. The H2 can be still adsorbed on the Be-G at 300 K via a MD simulation. The electrical field of -0.4 V/Å can further enhance the adsorption of the H2 . The Be-G is potential to be applied as a high-performance hydrogen gas sensor.